Does China's competitive generic substitution policy deliver equivalent clinical outcomes? A pilot study with two generic formulations of olanzepine - Chao Zhang; Yudan Ding; Zhenzhen Wu; Juan Wang; Xiangping Wu; Weiwei Xie (Frontiers Media S.A., 2023)
With the National Centralized Drug Procurement policy gradually applied nationally in China, concerns about the effectiveness and safety of bid-winning generic drugs are growing again, but relevant studies are lacking. This real-world, before-and-after study was conducted to explore the clinical effects of switching between two versions of generic olanzapine (one of them was bid-winning product). Pre-and post-switching serum olanzapine concentrations were compared. A total of 30 patients were included and results showed the log-transformed, dose-adjusted concentration of bid-winning generic olanzapine was significantly lower than that of another generic olanzapine, while no significant differences were shown on Clinical Global Impressions Severity of Illness or Improvement ratings before and after switching. This study suggest that a generic version of a psychotropic medication may not be of therapeutic equivalence or bioequivalence with another generic one. Changes in efficacy or tolerability are possible in every switch. Therapeutic drug monitoring could be a valuable tool during switches between generic drugs. Larger prospective clinical studies for other generic psychotropic medications in target populations are warranted.